Multidrug-resistant Nontyphoidal Salmonella Hotspots as Targets for Vaccine Use in Management of Infections in Endemic Settings. (15th February 2019) - Kariuki, Samuel; Mbae, Cecilia; Onsare, Robert; Kavai, Susan M; Wairimu, Celestine; Ngetich, Ronald; Ali, Mohammad; Clemens, John; Dougan, Gordon
Abstract: Background: Salmonella infections cause a disproportionately high number of deaths in Africa, especially among poor urban populations. The increasing level of multidrug-resistant (MDR) infections is a major cause of concern in these settings where alternative effective treatment is unavailable. Other options for management of these infections must be sought. The knowledge of hotspots in endemic settings can help to prioritize management and control measures in Kenya and the region. Methods: Using blood cultures, we investigated children presenting with fever of unknown origin for Salmonella infections. We performed antimicrobial susceptibility testing and whole genome sequencing to further characterize Salmonella isolates. Using Global Positioning System technologies, we mapped Salmonella isolates to households of patients in the study site and determined risk factors associated with high concentration of cases in particular sites. Results: A total of 281 Salmonella species (149 from blood and 132 from fecal samples) from febrile children <5 years of age were studied. These consisted of 85 Salmonella Typhimurium, 58 Salmonella Enteritidis, 32 other nontyphoidal Salmonella (NTS) serotypes, and 126 Salmonella Typhi. The prevalence of MDR invasive NTS (iNTS) was 77.2%, with 15% resistant to ceftriaxone, a drug that is last-line treatment for iNTS and other severe gram-negative infections in Kenya. Invasive NTS and S . Typhi together mapped around common water vending points and close to sewer convergence points in the highly populated village. Conclusions: These hotspots could be targeted for management and control strategies, including a combined introduction of typhoid and iNTS vaccines, aimed at reducing transmission in these endemic settings.